Exploration of food risk containing nitrosamine on potential public health implications: A descriptive literature review - Ariska Nandia Andriyani; Laila Fitria; Dewi Susanna (Universitas Gadjah Mada, 2024)
Purpose: Nitrosamines, chemical compounds formed from nitrites and amines, are gaining attention due to potential health risks. They are found in processed foods, such as cured meats, smoked fish, and fermented products, prompting a thorough examination of their sources and impact on health. This study aims to explore the nitrosamine content in food and its potential public health implications. Methods: This study employs a descriptive literature review methodology to investigate the impact of nitrosamine content in food on human health. It searches peer-reviewed journals, books, and online databases to identify relevant studies on food risk processing that contain nitrosamines and their impact on public health. Results: The review includes studies published over the past 20 years, focusing on nitrosamine content, nitrosamine formation processes, and health implications. Data from selected studies is systematically extracted and analyzed, focusing on patterns, risk factors, and health impacts, particularly in terms of cancer risk. Conclusion: This review found they pose significant public health risks, especially in meat products. Studies show a strong link between nitrosamine intake and increased risk of gastric and esophageal cancers. The detection and mitigation of nitrosamines are crucial, with more stringent regulations and improved testing techniques being needed in the food and pharmaceutical industries.